2010
DOI: 10.1002/mds.22922
|View full text |Cite
|
Sign up to set email alerts
|

Orodispersible sublingual piribedil to abort OFF episodes: A single dose placebo‐controlled, randomized, double‐blind, cross‐over study

Abstract: S90049, a novel sublingual formulation of the non-ergoline D(2)-D(3) agonist piribedil, has a pharmacokinetic profile promising to provide rapid relief on motor signs in Parkinson's disease (PD). We assessed the efficacy and safety of S90049 in aborting OFF episodes responding to subcutaneous apomorphine in PD patients with motor fluctuations. This was a single-dose double-blind double-placebo 3 x 3 cross-over study. Optimal tested doses were determined during a previous open-label titration phase (S90049 medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
0
15
0
3
Order By: Relevance
“…The present controlled study reinforces this treatment strategy with piribedil, another dopamine agonist. Although not marketed in several countries, piribedil was chosen in this study because of its broad use in France over several decades with well known safety profile and relatively low cost compared with more recent dopamine agonists, the fact that it is a non-ergot drug, its known efficacy on motor symptoms in Parkinson's disease but also based on early studies indicating a benefit on depression (Post et al, 1978;Castro-Caldas et al, 2006;Rascol et al, 2006Rascol et al, , 2010. Most importantly, in a previous study (Thobois et al, 2010) we had shown that dopamine withdrawal syndrome is related to mesolimbic dopaminergic denervation and we hypothesized that a D2/D3 agonist should be beneficial on non-motor psychic symptoms that we have classified as hypodopaminergic (Ardouin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The present controlled study reinforces this treatment strategy with piribedil, another dopamine agonist. Although not marketed in several countries, piribedil was chosen in this study because of its broad use in France over several decades with well known safety profile and relatively low cost compared with more recent dopamine agonists, the fact that it is a non-ergot drug, its known efficacy on motor symptoms in Parkinson's disease but also based on early studies indicating a benefit on depression (Post et al, 1978;Castro-Caldas et al, 2006;Rascol et al, 2006Rascol et al, , 2010. Most importantly, in a previous study (Thobois et al, 2010) we had shown that dopamine withdrawal syndrome is related to mesolimbic dopaminergic denervation and we hypothesized that a D2/D3 agonist should be beneficial on non-motor psychic symptoms that we have classified as hypodopaminergic (Ardouin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In a 7-month randomized double-blind placebo-controlled trial conducted in 405 patients with early PD, psychiatric disorders were reported with the same prevalence on piribedil (23 % of the patients) and placebo (18 %) [32]. Nevertheless, in the same study, hallucinations were among the most common reasons for discontinuation in the active group (4 patients, 1 %) as compared with placebo (none).…”
Section: Tolerability As Assessed In Clinical Trialsmentioning
confidence: 87%
“…Piribedil was reported to be effective in reducing the UPDRS III score at the first evaluation timepoint of 15 min, and in reversing the OFF state in 7 of 10 patients. In another study, the efficacy of an oro-dispersible sublingual formulation of piribedil for aborting OFF episodes was studied in 30 fluctuating PD patients by means of a randomized, double-blind, placebocontrolled crossover trial [32]. The primary endpoint was the maximal change versus baseline in UPDRS III assessed after drug administration following an overnight withdrawal of antiparkinsonian medications.…”
Section: Motor Fluctuationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was completed (11 instead of 14 per-protocol analysis set [PPAS] completers) soon after this reassessment of the primary end point variability indicated that the number of completed subjects was already sufficient to achieve minimum 80% power to detect the primary efficacy signal based on the initially assumed effect size. For testing MDS-UPDRS-III, assuming the effect size is 7 and SD of the paired difference is 12.6 [14, 29-31], a sample size of 22 subjects was initially projected to reach 81.1% power at a one-sided 0.05 significance level. …”
Section: Methodsmentioning
confidence: 99%